Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-32 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
The 5.5-year-old Nefeli after suffering an incomplete spinal cord injury Th10 by medical malpractice. B. Nefeli after eight months of conventional children rehabilitation in Switzerland (Affoltern). Sticks and orthosis were needed. C,D. Ten-year-old patient Nefeli after six months of coordination dynamics therapy. At school she can walk again and can write at the white board.